Annas Garten - Stahl, Lena; Thalmann, Johanna (Germany : FR Entertainment ; Framtidsbild, 2008)
Born in 1913, Anna Stahl looks back upon a life full of movement in an eventful century. She faces the questions asked by her granddaughter openly and meets the losses and unfulfilled desires of her past with a tremendous love for life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films